Experimental evidence of an increased leaf production in Prosopis after removal of epiphytes (Tillandsia) - Soria, Nicolas Franco (2014)
The production of new leaves of host trees can be affected by the presence of epiphytic species. This experimental study was planned to evaluate the effects on the mean number of new leaves produced by Prosopis alba considering the factors site-disturbance, different epiphytes loads, and the respective zones in the tree crown. The number of new leaves produced was counted manipulating branches with originally low and high loads of epiphytes at different crown zones, in 10 trees per site. The effect of manual removal of epiphytes on the leaf production of the hosts was analyzed by comparing branch responses in short and medium periods of time (i.e., 6 months and 3 years, respectively). There were no significant differences when comparing the number of new leaves produced in the sampled trees at sites with different human disturbance intensities. By contrast, significant differences were observed between both epiphytic loads treatments and when comparing tree crown zones. Experimental results showed a higher subsequent host leaf production (>100%) in branches where epiphytes were experimentally removed, in comparison with branches with high load of epiphytes The number of new leaves produced in branches with naturally low loads of the epiphytes was higher than 1000% compared to branches with high Tillandsia loads. Finally, a higher significant production of new leaves was observed in the bottom crown zone as compared with the middle and upper crown zones. Furthermore, this trend was confirmed considering a longer time-period (3 years) after experimental removal of epiphytes. A significant increase (>100%) was observed when comparing the production of new leaves between different periods after total epiphyte removal. In consequence, Tillandsia species could be considered as "structural parasites" of Prosopis alba.